Heart failure as a complication of COVID-19 infection: systematic review and meta-analysis. (14th October 2021) - Zuin, M; Zuliani, G; Roncon, L; Rigatelli, G
Abstract: Background: The prevalence and prognostic implications of heart failure (HF), as a complication of COVID-19 infection remains unclear. Aims: We performed a systematic review and metanalysis aimed to evaluate the pooled incidence of acute HF as a cardiac complication of COVID-19 disease and to estimate the related mortality risk in these patients. Methods: Data were obtained searching MEDLINE, Scopus and Web of Science for all investigations published any time to December 26, 2020. If statistical heterogeneity was 50%, the results were derived from the fixed-effects model otherwise the random-effects model. Results: Overall, 1064 patients [mean age 66 years, 618 males] were included in the final analysis reviewing six investigations. The cumulative in-hospital rate of COVID-19 patients complicated by acute HF ranged between 6.9 to 63.4% among the studies reviewed. A random effect model revealed a pooled incidence of COVID-19 patients complicated by acute HF in 20.2% of cases (95% CI: 11.1–33.9%, p<0.0001 I 2 =94.4%) (Figure 1, Panel A). A second pooled analysis, based on a random-effect model, confirmed a significant increased risk of death in COVID-19 patients complicated by acute HF during the infection (OR 9.36, 95% CI 4.76–18.4, p<0.0001, I 2 =56.6%) (Figure 1, Panel B). The Egger's tests revealed no evidence of publication bias in estimating both the primary and secondary outcome (t=0.058, p=0.956 and t=1.402, p=0.233, respectively). Meta-regression analysis, using age as moderator variable, failed in founding a statistically significant relationship with the incidence of acute HF onset as a complication of COVID-19 disease (p=0.062) or the mortality risk among the same subjects (p=0.053). Conclusions: Acute HF represents a frequent complication of COVID-19 infection associated with a higher risk of mortality in the short-term period. Funding Acknowledgement: Type of funding sources: None.